The Impact of Age on Mortality and Disability in Patients With Ischemic Stroke Who Underwent Cerebral Reperfusion Therapy: A Brazilian Cohort Study - Furlan, Natália Eduarda; Luvizutto, Gustavo José; Hamamoto Filho, Pedro Tadao; Zanati Bazan, Silméia Garcia; Modolo, Gabriel Pinheiro; Ferreira, Natalia Cristina; Miranda, Luana Aparecida; de Souza, Juli Thomaz; Winckler, Fernanda Cristina; Vidal, Edison Iglesias de Oliveira; de Freitas, Carlos Clayton Macedo; Martin, Luis Cuadrado; et al. (Frontiers in Aging Neuroscience, 2021)
Introduction: The main driver for increased stroke prevalence is the aging of the population; however, the best evidenced-based strategies for stroke treatment and prevention are not always followed for older patients. Therefore, the aim was studying the association of age with clinical outcomes (mortality and functional disability) in stroke patients who underwent cerebral reperfusion therapy at hospital discharge and 90 days after ictus. Methods: This was a retrospective (stroke databank analysis) cohort study of participants who had been diagnosed with ischemic stroke and undergone intravenous cerebral reperfusion therapy or mechanical thrombectomy. The variable of interest was patient age, which was categorized into four groups: (1) up to 59 years; (2) 60 to 69 years; (3) 70 to 79 years old; and (4) above 79 years. The primary outcome was mortality at hospital discharge and 90 days after stroke, and the secondary outcome was functional capacity at hospital discharge and 90 days after stroke. Results: A total of 281 patients was included in the study (235 treated by thrombolysis alone, and 46 treated with mechanical thrombectomy). The mean age of the total sample was 67±13.1 years. The oldest patients had the most unfavorable outcomes, except for mortality rate, at hospital discharge (mRS>2; OR: 1.028; 95% CI 1.005 to 1.051; p=0.017; mRS>3; OR: 1.043, 95% CI 1.018 to 1.069; p=0.001) and 90 days after stroke (mRS>2; OR: 1.028; 95% CI 1.005 to 1.051; p=0.017; mRS>3; OR: 1.043, 95% CI 1.018 to 1.069; p=0.001). Conclusion: Cerebral reperfusion was a viable treatment for ischemic stroke in both elderly and very elderly patients, as it did not increase mortality. However, it was observed that older individuals had worse functional outcomes at hospital discharge and 90 days after stroke.